Stability of 19-norandrosterone and 19-noretiocholanolone glucuronide in urine under various storage conditions - van der Merwe, PJ; Grobbelaar, E (South African Journal of Sports Medicine, 2003)
SA Sports Medicine Vol.15(2) 2003: 14-17